Outcome of Thoracic Column Antedisplacement and Fusion in Treatment of Thoracic Myelopathy Caused by Ossification of Posterior Longitudinal Ligament: A Case Series Study. Issue 3 (7th June 2021) - Ma, Xiangyang; Wang, Binbin; Chen, Yuyue; Ge, Su; Zou, Xiaobao; Zhang, Shuang; Xia, Hong
Abstract: BACKGROUND: Up to date, surgical outcome of multilevel thoracic ossification of posterior longitudinal ligament (T-OPLL) with high canal occupation ratio is less satisfactory. OBJECTIVE: To explore the result of thoracic column antedisplacement and fusion (TCAF) in treatment of multilevel T-OPLL with high canal occupation ratio. METHODS: A total of 5 patients who underwent TCAF procedure for T-OPLL were retrospectively reviewed. Parameters including extent of OPLL, thickness of the maximal OPLL (max-OPLL), maximal canal occupying ratio (max-COR) of OPLL, effective canal diameter (ECD) at the max-OPLL level, antedisplacement distance of thoracic columns, ASIA grades, Japanese Orthopedic Association (JOA) scores, and complications were collected and analyzed at preoperation and the last follow-up. RESULTS: All patients (5 F, mean age 61.0 yr, mean follow-up 18.0 months) underwent TCAF successfully and no spinal cord injury or cerebrospinal fluid leakage occurred. The mean extent of OPLL was 2.8 vertebral bodies. The mean preoperative thickness of the max-OPLL was 5.9 mm. The average antedisplacement distance of thoracic columns was 5.6 mm. The mean ECD was improved from 6.5 mm to 10.9 mm, and the max-COR was improved from 50.7% to 7.1% at last follow-up. Two patients showed improvement in ASIA grades and JOA scores were significantly improved from 5.6 points to 10.4 points at final follow-up. The overall therapeutic results of 1 patient were classified into good and 4 into fair at last follow-up. CONCLUSION: TCAF may be a safe and effective procedure in treatment of multilevel T-OPLL with high canal occupation ratio.